2014
DOI: 10.33588/rn.58s01.2013554
|View full text |Cite
|
Sign up to set email alerts
|

Estilos de disciplina y trastornos comórbidos de adolescentes con trastorno por déficit de atención/hiperactividad. Un estudio longitudinal

Abstract: trastorno por déficit de atención/hiperactividad Discipline styles and co-morbid disorders of adolescents with attention deficit hyperactivity disorder: a longitudinal study Introduction. Problems in cognitive functioning, social and educational development of children with attention deficit hyperactivity disorder (ADHD) continue to be present in adolescence and adulthood. Although the literature shows a significant relationship between the use of dysfunctional discipline methods and severity in the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Because the FAD roles subscale was detected as a significant unhealthy family condition, it may be interpreted that adequate parenting styles may not be present in these families compared with other families with children with ADHD. In the literature, it has been suggested that factors such as a lack of effective parenting skills, inappropriate parent-child interaction, and common usage of corporal punishment may be associated with both the presence and persistence of cognitive and behavioral problems, especially in the presence of ADHD and comorbid ODD 8,37,38 . Therefore, parameters such as the presence of negative family conditions, increased child-family conflict, relatively low social support, and domestic violence may be risk factors for the presence and severity of ADHD-C and oppositional symptoms 10,38 The maltreatment status data in our study were based on parental reports.…”
Section: Discussionmentioning
confidence: 99%
“…Because the FAD roles subscale was detected as a significant unhealthy family condition, it may be interpreted that adequate parenting styles may not be present in these families compared with other families with children with ADHD. In the literature, it has been suggested that factors such as a lack of effective parenting skills, inappropriate parent-child interaction, and common usage of corporal punishment may be associated with both the presence and persistence of cognitive and behavioral problems, especially in the presence of ADHD and comorbid ODD 8,37,38 . Therefore, parameters such as the presence of negative family conditions, increased child-family conflict, relatively low social support, and domestic violence may be risk factors for the presence and severity of ADHD-C and oppositional symptoms 10,38 The maltreatment status data in our study were based on parental reports.…”
Section: Discussionmentioning
confidence: 99%
“…Bajo condiciones experimentales se ha determinado que el establecimiento de sanciones tiene un impacto mesurable en la obediencia a la autoridad (Luna et al, 2017), mientras que el uso de recompensas positivas tiene un efecto significativo en la conducta prosocial (Carlo et al, 2016). Ambos aspectos están relacionados con la crianza y el establecimiento de normas, ya que la disciplina en el hogar se asocia con un mayor autocontrol de parte de los hijos, siempre que se aplique de forma afectiva y programada (Colomer-Diago et al, 2014). En tal sentido, el apoyo emocional y la empatía de los padres tiene un impacto significativo en la conducta prosocial de los hijos (Mestre et al, 2007), además, la comunicación con los padres y las emociones positivas están fuertemente asociados con la prosocialidad de los adolescentes (Ruvalcaba-Romero et al, 2018).…”
Section: Introductionunclassified